Flipped classroom in Indonesian higher education: A mixed-method study on students' attitudes and experiences - Ika Wahyuni Lestari (Universitas Syiah Kuala, 2021)
The flipped classroom has been widely applied in many educational settings. Thus, it is significant to understand how its implementation is perceived by students. This mixed-method study aimed to find out the fourth-year students' attitudes at a university in Indonesia on the flipped classroom they attended. It was also aimed at exploring their perception of the benefits and pitfalls they experienced when attending the flipped classroom. Employing a convergent mixed-method design, the quantitative data were obtained from 75 students (n=75) who were asked to complete a questionnaire. For the qualitative data, 13 students, divided into two groups, were invited to participate in a focus group interview to explore their experiences in attending the flipped classroom. The findings indicated that the students had positive attitudes towards the flipped classroom (M=2.87) and reported several benefits they perceived. Nonetheless, aspects regarding motivation (M=2.50) and the use of videos (M=2.49) and other technological supports indicated negative attitudes and were considered as pitfalls in the implementation of the model. Implications and recommendations were addressed for the better implementation of a flipped classroom.